The evolution of multi-level governance: The perspective on EU anti-crisis policy in Southern-European Eurozone states - Chrabąszcz, Robert; Zawicki, Marcin (Journal of Public Governance, 2016)
This article constitutes a presentation of the origin, rise and current state of multi-level governance (MLG) in the European Union. It presents theoretical considerations on the nature of MLG, its original, functional, normative and comparative uses, and the way in which these should be understood. While the path of evolution of MLG was linear prior to the financial crisis, it has been distorted subsequently by short- and long-term policies aimed at eliminating or alleviating the consequences of that crisis. While short-term interventions combine features typical for the original and functional uses of MLG, the long-term measures are typical for comparative and normative uses of the notion. This article therefore draws on the example of Southern-European Eurozone States in showing how the implementation of long-term preventative instruments operating in an anti-crisis role has hit obstacles in the form of institutional circumstances that are hard to overcome. Neglect of such domestic institutional contexts only increases the risk that the EU’s long-term anti-crisis policy will fail.